1984
DOI: 10.2166/nh.1984.0015
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Reduce Nitrate Content in Ground Water Used for Municipal Water Supply by Changing Agricultural Practices

Abstract: The heavy use of manure and fertilizers has in some parts of Sweden resulted in unacceptable concentrations of nitrate in ground water used for private and municipal water supply. In Halland for example, several of the municipal water supplies have nitrate concentrations close to 50 mg/I. Either anionic exchange or mixing with water with less nitrate are used to reduce the nitrate content in the distributed water. However, some wells have been abandoned because of high nitrate concentrations. In this study an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The nitrate leached out of the root zone can contammate groundwater supplies and present health related concerns. Leaching of nitrogen below the crop root zone has been reported by several investigators (Alberts and Spomer, 1985;Andersson et al, 1984;Baker, 1985;Baker and Johnson, 1981;Bergstorm' 1987;Burwell et al, 1976;Chichester, 1976;Kanwar et al, 1985b;Owens, 1987). Alberts and Spomer (1985) found that 85% of the NO3-N present in the soil profile was below 1.8 m in normally fertilized watersheds and positionally unavailable for crop uptake.…”
Section: Review Of Literaturementioning
confidence: 75%
“…The nitrate leached out of the root zone can contammate groundwater supplies and present health related concerns. Leaching of nitrogen below the crop root zone has been reported by several investigators (Alberts and Spomer, 1985;Andersson et al, 1984;Baker, 1985;Baker and Johnson, 1981;Bergstorm' 1987;Burwell et al, 1976;Chichester, 1976;Kanwar et al, 1985b;Owens, 1987). Alberts and Spomer (1985) found that 85% of the NO3-N present in the soil profile was below 1.8 m in normally fertilized watersheds and positionally unavailable for crop uptake.…”
Section: Review Of Literaturementioning
confidence: 75%
“…Bergstrom (1986) noted that fertilized (120 kg N ha-1 ) annual ryegrass intersown with barley (Hordeum distichum L.) reduced the mineral N content in the surface 1 m of soil by 23 kg N ha-l compared to similar treatments with-869 out ryegrass. Andersson et al (1984) observed mean nitrate levels of 50 kg N ha-l in the surface 1 m of soil in November after spring cereals had been grown, in contrast to levels of 9 kg N ha-1 following spring cereals undersown with grass.…”
mentioning
confidence: 81%
“…The more extensive root system of cereal rye, compared with other small grains, is an advantage when used as a cover crop for erosion control (Fribourg 1973). Various studies have demonstrated the utility of a cereal rye cover crop for weed control (Barnes and Putnam 1986;Bellinder et al 2004;Hinen and Worsham 1990;Mitchell and Teel 1977;Teasdale et al 1991;Zasada et al 1997) or to reduce nitrogen losses (Anderson et al 1984;Bergstrom 1986;Coale et al 2001;Shipley et al 1992). Zasada et al (1997) reported good common lambsquarters (Chenopodium album L.) control at densities between 20 and 40 weeds/m 2 with a cereal rye cover crop, but poor control at densities between 150 and 170 weeds/m 2 .…”
Section: Cover Cropmentioning
confidence: 99%